Determination of the Chemical Composition of Lithium Niobate Powders - Sanchez Dena, Oswaldo (2019)
Existent methods for determining the composition of lithium niobate single crystals are mainly based on their variations due to changes in their electronic structure, which accounts for the fact that most of these methods rely on experimental techniques using light as the probe. Nevertheless, these methods used for single crystals fail in accurately predicting the chemical composition of lithium niobate powders due to strong scattering effects and randomness. In this work, an innovative method for determining the chemical composition of lithium niobate powders, based mainly on the probing of secondary thermodynamic phases by X-ray diffraction analysis and structure refinement, is employed. Its validation is supported by the characterization of several samples synthesized by the standard and inexpensive method of mechanosynthesis. Furthermore, new linear equations are proposed to accurately describe and determine the chemical composition of this type of powdered material. The composition can now be determined by using any of four standard characterization techniques: X-Ray Diffraction (XRD), Raman Spectroscopy (RS), UV-vis Diffuse Reflectance (DR), and Differential Thermal Analysis (DTA). In the case of the existence of a previous equivalent description for single crystals, a brief analysis of the literature is made.